An experimental investigation of flow boiling heat transfer of R-134a in horizontal and vertical mini-channels - Saisorn, Sira; Kaew-On, Jatuporn; Wongwises, Somchai (My University, 2013)
Flow boiling experiments with R-134a flowing in horizontal and vertical mini-channels are performed to obtain flow visualization and heat transfer data. A 1.75mm diameter channel with a length of 600mm is used as test section. Two sets of the horizontal flow and vertical upward flow data are presented based on a mass flux range of 200-1000kg/m2s, a heat flux range of 1-80kW/m2 and a saturation pressure range of 7-13bar. Flow visualization and heat transfer results show heat transfer coefficient depending on flow pattern. The results also indicate that flow regime transition and heat transfer coefficient tend to depend on flow direction under the certain experimental conditions. In addition, the comparisons between the experimental data and the predictions recommended for either macro-scale flow boiling or micro-scale flow boiling are presented in this work. © 2012 Elsevier Inc.
Keywords: Flow boiling; Flow pattern; Heat transfer; Micro-scale channel